Nutritional Biochemistry Efficiency in Ruminants: A Meta-Analytical Perspective - Pacheco-Hernández, Armando (Asian Journal of Science, Technology, Engineering, and Art, 2025)
The present study is a meta-analysis of the literature on nutritional biochemical efficiency in ruminants, based on publications between 2020 and 2024. The main objective was to evaluate how the digestion and absorption of nutrients, such as proteins, fibers and carbohydrates, impact the health and productivity of ruminants, including cattle, sheep and goats. Twenty-five studies were selected that met the inclusion criteria, such as the use of quantitative data and the availability of nutritional indicators, such as digestibility and volatile fatty acid (VFA) production. Dietary interventions, such as the addition of prebiotics and digestive enzymes, were analyzed to determine their effect on nutritional efficiency. Prebiotics, such as inulin and fructooligosaccharides (FOS), improved fiber digestibility by 12%, while enzymes showed a more variable improvement of 8% in carbohydrate digestibility. The study used statistical tools to assess heterogeneity between studies and robustness of results. Considerable variability in ruminant response to digestive enzymes was identified, and subgroup analysis indicated that species influences the effects of dietary interventions. Although publication bias was not significant, it is recommended that future research publish both positive and negative results to improve overall understanding of interventions. It is concluded that personalized diets, based on species-specific needs, can optimize nutritional efficiency in ruminants.